Pultruded materials and structures: A review. (November 2020) - Vedernikov, Alexander; Safonov, Alexander; Tucci, Fausto; Carlone, Pierpaolo; Akhatov, Iskander
Currently, the application of pultruded profiles is increasing owing to their advantages, such as light weight, high strength, improved durability, corrosion resistance, ease of transportation, speed of assembly, and nonmagnetic/nonconductive characteristics. This review analyzes the main application fields of elements produced by pultrusion manufacturing processes: bridges and bridge decks, cooling towers, building elements and complete building systems, marine construction, transportation, and energy systems. Analysis of the scientific literature in relation to the mechanical behavior of pultruded elements is presented as well. Finally, this review outlines the future study possibilities, giving the researchers and practitioners the directions for deeper investigation of specific features and exploration of new ones concerning the mentioned aspects of pultruded fiber-reinforced polymer composites.